Exploring the development of student teachers interest in educational technology through Interest-Driven Creator theory - Wong, Su Luan; Md. Khambari, Mas Nida; Wong, Lung Hsiang; Tang, Sai Hong (Asia-Pacific Society for Computers in Education, 2023)
This qualitative study is one of the early attempts to provide empirical evidence to inform Interest-Driven Creator (IDC) theory through a discrete Educational Technology course. In this study involving 64 undergraduate students who majored in education, we focused on the interest loop (triggering, immersing and extending) as it acts as an impetus to nurturing habitual learners. Qualitative data were sought to answer two research questions that explored student teachers’ initial interest in learning educational technology and to understand the development of their interest using IDC as the underpinning theory. The findings indicated that they initially showed little interest in the course. However, others felt good about and were drawn towards educational technology. The findings also indicated that interest development begins when situational interest is triggered and they become aroused by the course contents. The student teachers then willingly spend time accomplishing the given task when immersed in the learning process with a clear goal. They then progress to extend their interest, making sense of their newly acquired knowledge and connecting with other previously known knowledge to expand it further. Overall, our findings suggested that the interest loop of IDC was able to describe the development of student teachers’ interest in educational technology.